Communication of Diagnosis of Infertility: A Systematic Review - Mosconi, Laura; Crescioli, Giada; Vannacci, Alfredo; Ravaldi, Claudia (Frontiers in Psychology, 2021)
Background: When infertility is diagnosed, physicians have the difficult task to break bad news. Their communication skills play a central role in improving patients’ coping abilities and adherence to infertility treatments. However, specific guidelines and training courses on this topic are still lacking. The aim of the present study is to provide some practical advice for improving breaking bad news in infertility diagnosis through a systematic literature review of qualitative and quantitative studies. Methods: Electronic searches were performed in the MEDLINE, Embase, PsycINFO, CINHAHL, and Psychology and Behavioral Sciences Collection databases. All articles focusing on the communication of the diagnosis of infertility were included. The main findings of each included article were then summarized. Results: Literature search identified 11,838 references that were screened for eligibility. Full texts of 81 articles were retrieved, and their analysis led to the inclusion of 4 articles, which treated the theme of communication of infertility only partially. The main addressed aspects concerning the communication of the infertility diagnosis were: (i) the value patients give to healthcare professionals’ communication skills; (ii) the importance of giving clear information on diagnostic procedures and treatments in order to decrease patients’ anxiety; (iii) the importance of involving both partners. Conclusions: This review pointed out that the communication of the infertility diagnosis is still under-investigated. Specific guidelines are currently not available, but other protocols could be used. Taking into account the principal aspects of communication highlighted with this review, in this study we suggested an adaptation of the original SPIKES protocol that could be used by healthcare professionals for the communication of the infertility status.